Unveiling Hate Speech Dynamics: An Examination of Discourse Targeting the Spanish Meteorological Agency (AEMET) - Sergio Arce-García; Virginia Martin-Jiménez; Leticia Rodríguez-Fernández (Social Inclusion, 2025)
This article examines hate speech directed at AEMET, the Spanish meteorological state agency, on the social media platform X. We analysed nearly half a million messages posted between 31 December 2021 and 19 April 2023, using hate speech detection algorithms, text mining techniques, and qualitative analysis to identify patterns and themes in the discourse. Our research reveals a troubling reality, with around 25% of the messages collected displaying some degree of hostility towards AEMET, its staff, and its scientific work. A considerable amount of hate speech was expressed through derogatory comments and insults aimed at meteorologists, which is indicative of a wider trend of anti‐intellectualism and scepticism of scientific expertise. Furthermore, the spread of conspiracy theories, particularly those related to geoengineering and chemtrails, highlights the spread of misinformation within online communities. This study emphasises the importance of acknowledging and addressing the spread of hate speech in meteorology and scientific communication. By emphasising the negative effects of such language on public perception and trust in scientific institutions, this article advocates for collaborative efforts to promote a culture of informed dialogue and evidence‐based discourse. The results highlight the importance of combating hate speech and misinformation to protect the integrity and credibility of scientific institutions such as AEMET.